Racial conflict resolution and power sharing in Guyana : selected readings - Karran, Kampta (Offerings Pub. Belle Vue Pilot SchemeGY, 2004)
Focuses on racial conflicts during the period 1831-1905. Looks at the consequences of the 1992 election. Examines local government and the growth of inter-ethnic cooperation in Guyana, as well as power sharing in a plural society.